Socio-spatial transformation of neighbourhoods around rail transit stations: an experience from Tehran, Iran - Forouhar, Amir; Zamani, Bahador; Rafieian, Mojtaba (Bulletin of Geography. Socio-economic Series, 2022)
While increasing evidence suggests that rail infrastructure plays a structuring role in shaping and transforming cities and regions over time, empirical studies on the simultaneous development of rail infrastructure and socio-spatial transformation of surrounding neighbourhoods, especially at a local scale, are scarce. The main aim of the article is to evaluate the transformation of neighbourhoods around rail transit stations, as well as provide a possible explanation of how neighbourhoods can be differently affected by the presence of rail stations. Based on a longitudinal dataset (2006–16) and using a Difference-in-Differences (DID) model and Multivariate Analysis of Variance (MANOVA), a comparative analysis of the Tehran Metro Rail System (TMRS) is conducted between high-income neighbourhoods and low-income neighbourhoods of the city. The results yield that the northern, high-income neighbourhoods and the southern, low-income neighbourhoods of Tehran have been transformed heterogeneously in terms of socio-demographic factors, land-use conditions and renewal processes. The findings also indicate that the mixed estimated transformation of neighbourhoods around TMRS’s stations could be explained by the contextual factors of the northern and southern study settings in Tehran, including land-use characteristics and socio-economic factors.